2017
DOI: 10.1016/j.biombioe.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Using a chelating agent to generate low ash bioenergy feedstock

Abstract: Inorganic elements present in lignocellulosic biomass and introduced during harvesting and handling of the feedstock negatively affect biomass conversion to fuels and products. In particular, alkali and alkaline earth metals act as catalysts during thermochemical conversion, contribute to reactor degradation, and decrease the yield and quality of the reaction products. In this study, we investigated an approach to reduce ash content of switchgrass. Several reagents (chelating agents ethylenediaminetetraacetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…This supports the replacement of EDTA with the more environmentally friendly chelating agents PDA and HEDP for removal of copper and biomass inherent inorganics. Additionally, it is noteworthy to point out that both potassium and sodium are completely extracted from the ties using only water, which is consistent with what has been reported in the literature . With all chelating agents, as well as with water, extraction efficiency significantly decreases with increasing thermal desorption severity.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This supports the replacement of EDTA with the more environmentally friendly chelating agents PDA and HEDP for removal of copper and biomass inherent inorganics. Additionally, it is noteworthy to point out that both potassium and sodium are completely extracted from the ties using only water, which is consistent with what has been reported in the literature . With all chelating agents, as well as with water, extraction efficiency significantly decreases with increasing thermal desorption severity.…”
Section: Resultssupporting
confidence: 89%
“…Although thermal treatment is an effective method for recovery of the organic fraction of wood preservatives, CN contains an additional inorganic fraction not found in creosote that remains in the biomass after desorption. Many inorganics such as alkali and alkaline earth metals in particular have been reported to possess undesired catalytic effects on thermochemical conversion processes such as pyrolysis. The presence of copper and these other metals leads to a decrease in yield and intensification of physical and chemical issues such as slagging, clogging, and degradation of reactor walls from corrosion and deactivation of catalysts . Chelating agents are often used as an extraction method for the removal of inorganics from biomass, including those that have these detrimental effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignocellulosic biomass is a complex mixture of organic (cellulose, hemicellulose, lignin, etc.) and inorganic (ash) substances, and an increase in the number of fibrous compounds can lead to an increase in ash content [ 21 ]. Additionally, the application of hydrated lime to cattle bedding for disinfection purposes (personal communication with the farm owners) appears to have contributed to the high fixed solids content of CM.…”
Section: Resultsmentioning
confidence: 99%
“…(without degrading hemicellulose, cellulose, and lignin). For instance, Edmunds et al (2017) found that ethylenediaminetetraacetic acid (EDTA) nearly completed extraction of alkali and alkaline earth metals such as K, Ca, and Mg, and high removal of S and Si of switchgrass by using a microwave-assisted extraction method. Besides, nitrilotriacetic acid (NTA) and ethylenediiminopropanedioic acid (EDDM) are biodegradable comparing to EDTA.…”
Section: Leaching With Chemicalsmentioning
confidence: 99%